Synthesis, Crystal Structures and Photoluminescent Properties of One-Dimensional Europium(III)- and Terbium(III)-Glutarate Coordination Polymers, and Their Applications for the Sensing of Fe3+ and Nitroaromatics - Hussain, Sajjad; Chen, Xuenian; Harrison, William T. A.; Elsegood, Mark R. J.; Ahmad, Saeed; Li, Shujun; Muhammad, Shabbir; Awoyelu, David (Frontiers in Chemistry, 2019)
Two lanthanide–glutarate coordination polymers, viz.: {[Eu(C5H6O4)(H2O)4]Cl}n, (1) and [Tb(C5H7O4)(C5H6O4)(H2O)2]n, (2) have been synthesized and characterized by IR spectroscopy, thermogravimetric analysis and X-ray crystallography. In 1, the Eu(III) ions are coordinated by four O atoms from two bidentate chelating carboxylates, one O atom from a bridging carboxylate and four O atoms from water molecules adopting an EuO9 muffin shaped coordination geometry. In 2, the Tb(III) ions are coordinated by six O atoms from three bidentate chelating carboxylates, one O atom from a bridging carboxylate and two O atoms from water molecules to generate muffin like TbO9 polyhedron. In both compounds, the metal polyhedra share edges, producing centrosymmetric Ln2O2 diamonds, and are linked into [001] chains by bridging glutarate di-anions. The crystal structures are stabilized by O–HO and O–HCl hydrogen bonds in 1, and O–HO hydrogen bonds in 2. Compound 1 exhibits a red emission attributed to the 5D0 → 7FJ (J = 1–4) transitions of the Eu(III) ion, whereas 2 displays green emission corresponding to the 5D4 → 7FJ (J = 0–6) transitions of the Tb(III) ion. Both the compounds exhibit high sensitivity and selectivity for Fe3+ ions due to luminescence quenching compared to other metal ions, which include; Na+, Mg2+, Al3+, Cr3+, Mn2+, Fe2+, Co2+, Ni2+, Zn2+ and Cd2+. Compounds 1 and 2 also show high luminescence quenching sensitivity for 4-nitrophenol over the other aromatic and nitroaromatic compounds, namely; bromobenzene, 1,3-dimethylbenzene, nitrobenzene, 4-nitrotolune, 4-nitrophenol, 2,6-dinitrophenol and 2,4,6-trinitrophenol.